Effects of construction disturbances on tunnel displacement and the protective role of soil reinforcement in metro tunnels - Haomin Wang; Mushuang Lin; Jianbo Li; Hengyu Wang; Xifeng Fu; Chaohui Zhong (Scientific Reports)
Abstract This paper analyzes the effects of construction disturbances on tunnel displacement and the protective role of soil reinforcement in metro tunnels through laboratory tests and numerical simulation. Initially, disturbance zones were delineated for a specific project in Zhejiang Province based on the unloading ratio and field disturbance tests conducted at the Gaotangqiao metro station excavation site in Ningbo. The primary soil layer at the project site, silty clay, was artificially disturbed by incorporating salt grains and different amounts of cement into remolded soil. Uniaxial and triaxial tests were conducted to examine the engineering properties of disturbed and natural soils. The relationship between the cement content and the disturbance degree was established and verified through compressibility, shear strength, and structural yield stress indices, from which the parameters for the Hardening Soil Model with Small Strain Stiffness (HSS) were obtained. The impact of pit excavation construction on tunnel displacement was analyzed using Plaxis3D, taking into account the degradation of soil properties due to construction-induced disturbance. Additionally, the impact of disturbances from soil reinforcement construction on the protective efficacy for metro tunnels was systematically evaluated. The results show that with a cement content of 2%, the compression index, shear strength index, and structural yield stress were essentially equivalent to those of the undisturbed soil. The vertical displacement of the tunnel increased by 18.3% due to construction disturbances. During the construction of the foundation reinforcement, concrete mixing piles and tunnel grouting caused disturbances in the foundation soil, leading to additional displacements of the tunnel, with tunnel grouting showing the most significant disturbance-induced displacement. The portal reinforcement method was identified as the most effective at minimizing tunnel deformation, offering substantial protection with minimal intervention and ease of implementation.